2016
DOI: 10.1007/s13205-016-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of shelf life of soymilk using immobilized protease of Oerskovia xanthineolytica NCIM 2839

Abstract: Protease enzyme has lot of commercial applications, so the cost-effective production of protease using sunflower oil seed waste was carried out from Oerskovia xanthineolyitca NCIM 2839. The maximum protease production was after 24 h of incubation with 2.5 % oil seed waste concentration. O. xanthineolytica was found to produce two proteases—P1 and P2. The proteases were purified using 60 % cold acetone precipitation and DEAE-cellulose ion exchange chromatography. SDS-PAGE revealed molecular weight of P1 and P2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Carbohydrase treatment (1.2% Celluclast 1.5 L, 3 h) improves the physical stability of soybean drinks during storage and ameliorates bean flavor [117]. It is generally believed that proteolysis will release low-molecular-weight peptides, resulting in bitter taste, but when Sahoo et al immobilized two non-commercial proteases derived from sunflower seeds, added them to soybean drink, and incubated them at 30 • C for 1 h, they found that the beany smell decreased and the pleasant smell increased [118]. Low-molecular-weight peptides produced after proteolysis are primarily composed of hydrophobic amino acids.…”
Section: Enzymatic Processingmentioning
confidence: 99%
“…Carbohydrase treatment (1.2% Celluclast 1.5 L, 3 h) improves the physical stability of soybean drinks during storage and ameliorates bean flavor [117]. It is generally believed that proteolysis will release low-molecular-weight peptides, resulting in bitter taste, but when Sahoo et al immobilized two non-commercial proteases derived from sunflower seeds, added them to soybean drink, and incubated them at 30 • C for 1 h, they found that the beany smell decreased and the pleasant smell increased [118]. Low-molecular-weight peptides produced after proteolysis are primarily composed of hydrophobic amino acids.…”
Section: Enzymatic Processingmentioning
confidence: 99%
“…Two non-commercial proteases from residual sunflower seeds were immobilized in calcium alginate spheres and incorporated into soymilk for enzymatic treatment at 30 °C for 1 h; this resulted in a product with reduced bean aroma and an increase in pleasant smell, in addition to an increased shelf life of 15 days compared to the 10 days of the non-treated sample. This was most likely due to the antimicrobial peptides released by enzymatic hydrolysis (Sahoo, Gaikwad, Ranveer, Dandge, & Waghmare, 2016).…”
Section: 42ultra-high-pressure Homogenizationmentioning
confidence: 99%